Revealing Healthcare Patterns: Data Mining and Machine Learning in Electronic Health Records Analysis - Purna Chandra Rao Kandimalla (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research paper delves into the extensive exploration of uncovering concealed trends and patterns within healthcare data. The primary objective is to reveal obscured insights present within diverse clinical information reports, including electronic health records, imaging scans, and patient histories. Employing data mining methodologies, this study aims to extract invaluable knowledge with the potential to significantly enhance the efficiency of diagnostic procedures and treatment plans in the healthcare domain. In the current healthcare landscape, a surge in data generation has created an unprecedented opportunity at the crossroads of data mining and machine learning within the healthcare industry. The core purpose of this study is to conduct a comprehensive investigation into the symbiotic relationship between data-driven methodologies and the medical field. Emphasizing the most recent trends and advancements, the research rigorously assesses the potential impact of machine learning techniques. Through this examination, the aim is to redefine the fundamental nature of healthcare provision by exploring practical and feasible applications within the medical domain. This exploration seeks to illuminate the promising future of data-driven methodologies, steering healthcare towards a more patient-centered, financially sustainable, and operationally efficient paradigm.